Fracionamento da lignina Kraft e aplicação em diferentes segmentos: Desenvolvimento de aditivo com propriedades de barreira e hidrogéis para remoção de metais potencialmente tóxicos - Lima, Vitor Hugo de (Universidade Federal de São Carlos, 2023)
This study elucidates the significance of the Kraft lignin (KL) fractionation process to obtain less polydisperse fractions for application in the development of novel materials or integration of lignin fractions into the processing of everyday materials. Two fractions, at pH 7.5 (KL75) and pH 4.5 (KL45), were obtained from KL using the fractionation method via acid gradient precipitation from the aqueous medium. The process efficiently separated the fractions, which exhibited distinct properties and characteristics when investigated through techniques such as gel permeation chromatography (GPC), thermal properties via thermogravimetric analysis (TGA) and differential scanning calorimetry (DSC), Fourier-transform infrared spectroscopy (FTIR), and 31P nuclear magnetic resonance spectroscopy (NMR); morphology was analyzed through scanning electron microscopy (SEM).The fractions were employed in the development of an additive with barrier properties and hydrogels for the removal of potentially toxic metals in aqueous environments. For the formulation of a barrier additive, lignin fractions were combined with starch to prepare a film-forming solution, which was subsequently applied using the tape casting technique to produce thin films. The structural, morphological, mechanical, thermal, and water vapor permeation characteristics of the films were characterized. Hydrogels were produced through the crosslinking of lignin with starch using ethylenediaminetetraacetic acid (EDTA) as the crosslinking agent and triethylamine as a catalyst. The development of these materials using lignin fractions proved promising based on the obtained results. The KL45 fraction exhibited superior barrier properties compared to KL75 and KL, albeit with inferior thermal and mechanical properties. KL75 demonstrated enhanced swelling properties and adsorption capacity for metals such as copper (Cu) and mercury (Hg) when dispersed in an aqueous medium from sulfur salts (S) such as copper sulfate (CuSO4) and mercury sulfate (HgSO4). The results obtained for these novel materials reinforce positive expectations regarding the use of lignin as a raw material for higher value-added materials with the potential to replace products derived from non-renewable sources.
Kraft lignin fractionation and application in different segments: Development of additive for barrier properties and hydrogels for removing potentially toxic metals
Keywords: Lignina; Fontes Renováveis; Propriedades de Barreira; Hidrogéis; Lignin; Renewable Sources; Barrier Properties; Hydrogels; CIENCIAS EXATAS E DA TERRA::QUIMICA; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::MATERIAIS NAO METALICOS; ENGENHARIAS::ENGENHARIA QUIMICA::TECNOLOGIA QUIMICA; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::MATERIAIS NAO METALICOS::POLIMEROS, APLICACOES; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA ORGANICA::POLIMEROS E COLOIDES; CIENCIAS AGRARIAS::RECURSOS FLORESTAIS E ENGENHARIA FLORESTAL::TECNOLOGIA E UTILIZACAO DE PRODUTOS FLORESTAIS::QUIMICA DA MADEIRA; ENGENHARIAS::ENGENHARIA QUIMICA::TECNOLOGIA QUIMICA::PAPEL E CELULOSE; ENGENHARIAS::ENGENHARIA QUIMICA::TECNOLOGIA QUIMICA::POLIMEROS